Viability of integrating Solar Water Heating systems into High Energy Performance housing in Algeria. (15th April 2018) - Sami, S.; Semmar, D.; Hamid, A.; Mecheri, R.; Yaiche, M.
Abstract: In the framework of the new Algerian energy policy, we investigate in this contribution the energetic and the economic viability of the integration of Solar Water Heating (SWH) systems into High Energy Performance (HEP) housing in Algeria. The case studies are houses situated in four different locations each one representing a distinct Algerian climatic zone. In order to efficiently design the SWH systems to be installed, we use a simple method based on the determination of the optimum collector area that minimizes the costs of the installation via considering both economic factors and system parameters. The solar fraction, needed for this analysis, has been calculated using the F-Chart method with monthly meteorological data characterizing each region. The results revealed very promising high values of the solar fraction in almost all the studied regions and that an adequate funding policy will permit to establish a good balance between system performance and system design resulting in a higher competitiveness of solar energy against conventional energy. Highlights: Design analysis of SWH systems used in Algerian residential sector is presented. Calculated solar potential can cover 45–100% of hot water demand in all regions. Optimum conditions satisfying minimum operating costs of the system are given. Ending electricity funding policy is essential for a profitable solar investment. Savings in conventional energy use can reach 46% in the north and 57% in the south.